Uses and Gratifications Theory dalam Media Sosial WA (WhatsApp) - Ludwiq Suparmo (Communicology: Jurnal Ilmu Komunikasi, 2017)
It has been known for decades that the conventional mass communications have been eroded and transformed due to the information technology into advanced means of communication. One of these has become viral as the social media through WA (whatsApp) application, which surely has brought a phenomenal effect on the uses and gratifications theory that was more applied on mass communications. The research based on a qualitative methodology exploring to several WA Groups has revealed the rank of uses and gratification in using the WA social media.